Evaluating the efficacy and safety of Ātrilāl (Ammi majus L.)against Psoralen in Vitiligo: a single-blind, parallel-group randomized controlled trial (Bangladesh Journal of Medical Science, 2026)
Objectives Vitiligo is a common skin disorder characterized by focal failure of pigmentation due to the destruction of melanocytes mediated by immunological mechanisms. Ātrilal (Ammi majus L.), a plant drug, is used traditionally for the treatment of vitiligo. However, clinical studies showing its safety and efficacy are lacking. This study aimed to evaluate the efficacy and safety of Ātrilal against Psoralen on depigmented vitiliginous skin. Materials and methods This randomized active controlled study was conducted on the participants diagnosed with vitiligo. The participants in the test group were treated with Ātrilal (1500 mg) thrice daily orally and Ātrilal powder mixed with vinegar applied topically on vitiliginous lesions on alternate days followed by sun exposure for 16 weeks. The participants in the control group received methoxsalen tablets (20-40 mg) orally on alternate days and Methoxsalen (1%) solution was applied topically in the morning, followed by sun exposure. The outcome measures were the change in VASI, IGA, and PGA scores from baseline to post-treatment. Results In the test group, VASI (mean ± SD) reduced by 48.27% from 2.9±0.65 to 1.5±0.67. In the control group, VASI (mean ±SD) improved by 42.42% from 3.3±1.5 to 1.9±1.5. The difference in VASI in both test and control groups were found statistically and clinically significant. The test drug did not show any adverse drug reaction or change in haematological and biochemical parameters from baseline to post-treatment. Conclusion Ātrilal was found safe, effective and tolerable herbal treatment for depigmented vitiliginous skin in vitiligo. [Registration Number: CTRI/2019/04/018669 dated 18/04/2019].Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 963-973